A Nanopatterned Cantilever Device for Assaying Contractile Properties of Stem Cell-Derived Cardiomyocytes - Lih, Daniel Chen (My University, 2016)
Drug-induced cardiotoxicity has been a major issue for both patients and pharmaceutical companies. Current in vitro cardiotoxicity screening utilizes genetically modified cell lines, which do not recapitulate adult human cardiomyocytes in terms of their biochemical and electro-physical phenotype. More recently screening technologies have utilized single-cell assays based on human stem cell-derived cardiomyocytes; however, measurements from single cells are incapable of predicting the cardiotoxic effects of drugs at the tissue level. The discrepancy in cell characteristics between in vitro culture and native human myocardial tissue has resulted in the release of potentially lethal drugs and the loss of potentially valuable drugs. To improve the accuracy and efficacy of preclinical cardiotoxicity screening, efforts have been made to create in vitro assays that measure the cardiomyocytes’ contractility, in order to better represent the overall response of the heart to drug treatment. Here we present a device for assaying the contractile properties of stem cell- derived cardiomyocytes using flexible, nanopatterned cantilevers and aligned cardiac tissue inspired by the structure of native myocardial tissue. Studies have shown that the nanoscale extracellular-matrix fibers play an important role in the alignment, development, and function of native heart tissue. We demonstrate a greater extent of cell alignment and cytoskeletal alignment as compared to unpatterned cantilevers thereby more closely mimicking native tissue structure. This demonstrates the benefits of nanopatterns in guiding the development of cardiomyocytes in vitro. We also investigated the contractile development of cantilevers over time and in response to treatment with a known cardiotoxic drug. By characterizing the stress of cantilevers in response to cardiomyocyte contraction, a more direct representation of how cardiotoxicity affects the functionality of cardiac tissue is realized.
Thesis (Master's)--University of Washington, 2016-01
Keywords: Cantilevers; Cardiomyocytes; Contractility assay; Drug-induced cardiotoxicity; Nanotopography; Stem cell-derived cardiomyocytes; Biomedical engineering; Cellular biology; Nanotechnology; bioengineering